Arm function after stroke: measurement and recovery over the first three months. Issue 6 (June 1987) - Heller, A; Wade, D T; Wood, V A; Sunderland, A; Hewer, R L; Ward, E
Abstract : Four short, simple measures of arm function, suitable for use with patients recovering from acute stroke, are described. These tests are: the Frenchay Arm Test, the Nine Hole Peg Test, finger tapping rate and grip strength. Good interobserver and test-retest reliability was demonstrated for all tests, and the Frenchay Arm Test was shown to be valid. Normal values for all tests were established on 63 controls. It was found that the limited sensitivity of the Frenchay Arm Test could be improved using the Nine Hole Peg Test and grip strength. Recovery of arm function has been studied in a sample of 56 patients seen regularly over the first 3 months after their stroke, using these standard measures. The results demonstrated a wide variation in recovery curves between patients. The use of the Nine Hole Peg Test enabled further recovery to be detected after patients achieved a top score on the Frenchay Arm Test. Failure to recover measureable grip strength before 24 days was associated with absence of useful arm function at three months. Measurement of finger tapping rate was not useful.